Optimum Dispatch of Active and Reactive Generation by Quadratic Programming - Nicholson, H.; H. Sterling, M. J. (IEEE transactions on power apparatus and systems, 1973)
Optimum scheduling of generation subject to constraints on maximum and minimum levels and rates of change of generation, spare capacity and line flow limits, is studied. A linear programming formulation for system constraints is used with a quadratic cost function for generation and transmission line loss. An optimal solution for real power dispatch is obtained by quadratic programming, and optimum allocation of reactive power is based on a gradient technique which minimises transmission loss subject to nodal voltage and reactive power limits. An ac load flow analysis is incorporated together with a load prediction program based on a spectral analysis of past load data. The feasibility of simulating the overall system problem, including load-frequency control of equivalent generation, using a combined analogue-digital process computer system linked to a large scientific digital computer by data link is investigated.